Candida infection in oral leukoplakia: an unperceived public health problem. (2nd October 2016) - Dilhari, Ayomi; Weerasekera, Manjula M.; Siriwardhana, Anusha; Maheshika, Oshanthi; Gunasekara, Chinthika; Karunathilaka, Sunil; Nagahawatte, Ajith; Fernando, Neluka
Abstract: Objectives: The study aimed to determine the proportion, known risk factors and etiology for Candida infection in leukoplakia lesions among patients with oral leukoplakia attending the Oral and Maxillofacial Clinic at a Tertiary Care Hospital in Sri Lanka. Materials and methods: Eighty clinically suspected oral leukoplakia patients were included. Two oral swabs each, from leukoplakia patients: one swab from the lesion and the other one from the contralateral unaffected corresponding area (as a control) were collected. Direct microscopy and culture followed by colony count and phenotypic identification were performed to identify pathogenic Candida species. Results: Candida infection was seen in 47% of patients with oral leukoplakia. Candida albicans (94.7%) was the most common Candida species followed by Candida tropicalis (5.3%). Majority of Candida -infected lesions were seen in the buccal mucosa region. Alteration of taste ( p  = 0.021), having other oral lesions ( p  = 0.008), angular cheilitis ( p  = 0.024) and periodontitis ( p  = 0.041) showed a significant association with Candida -associated leukoplakia. Increasing age showed a significant tendency for Candida infection ( p  = 0.020). Smoking ( p  = 0.026) and betel-quid chewing ( p  = 0.006) were also found to be significantly associated, although alcohol consumption alone did not show a significant association. Oral leukoplakia patients who had all three habits: alcohol consumption, smoking and betel-quid chewing had a significant association with Candida infection ( p  = 0.004). Conclusions: Patients who had a combination of risk factors: smoking, betel-quid chewing and alcohol consumption were seen to have a significant association with Candida infection. Further betel-quid chewing alone and smoking singly was also significantly associated with Candida infection in oral leukoplakia.